The case for investment in nutritional interventions to prevent and reduce childhood and adolescent overweight and obesity in Peru: a modelling study - Maria Elena Ugaz; Christina L. Meyer; Angela M. Jackson-Morris; Daphne Wu; M. Michelle Jimenez; Carlos Rojas-Davila; Carlos Orlando Zegarra Zamalloa; Elizabeth F. Ludwig-Borycz; D'Arcy Williams; Jo Jewell (BMC, 2024)
Abstract Background Between 2006 and 2016 the prevalence of overweight and obesity among children and adolescents aged 5-19 years in Peru increased from 22.7 to 27.0%. This investment case quantifies the economic impacts of childhood and adolescent overweight and obesity in Peru. It identifies and quantifies the potential impact of a set of new or expanded interventions that can strengthen current national efforts to prevent and reduce child and adolescent overweight and obesity. Methods A deterministic Markov cohort model with a societal cost perspective estimated reductions in mortality and morbidity from implementing interventions to prevent and reduce child and adolescent overweight and obesity and the impact in savings in healthcare costs and gains in wages and productivity. Interventions identified through a review of published literature includes a school-based social marketing campaign, exclusive breastfeeding promotion and support, a healthy food and drink policy for school premises, and a 20% subsidy on fruits and vegetables for people living below the national poverty line. The return on investment (ROI) was calculated along with the estimated cost savings associated with the interventions. Analysis was conducted to test ROI sensitivity to changes in the key parameters and assumptions. Results Between 2025 and 2092, the expected combined direct and indirect healthcare costs attributable to child and adolescent overweight and obesity in Peru are 210.6 billion USD. The direct healthcare costs are 1.8 billion USD, and the indirect costs are 208.8 billion USD. Expected savings for all interventions combined is 13.9 billion USD with a per-person savings of 12,089.8 USD. The expected ROI of the four interventions combined is 39.3 USD (30-years), 64.6 USD (50-years), and 164.1 USD (66-years) per one USD invested. Conclusions The overweight and obesity epidemic among children and adolescents in Peru requires wide-ranging and expanded implementation of policies to achieve long-term reductions in prevalence. This study's findings show that the four priority interventions have high ROIs and can be used to guide policy to address the complex interplay of factors that contribute to the obesogenic environment.